2007
DOI: 10.1377/hlthaff.26.3.w338
|View full text |Cite
|
Sign up to set email alerts
|

Location, Location, Location: Residence, Wealth, And The Quality Of Medical Care In Delhi, India

Abstract: There are seventy medical care providers within walking distance of every household in Delhi. However, inequalities in health outcomes persist among the rich and poor, which might reflect differences in the quality of available care. This paper shows that providers visited by the poor were indeed less knowledgeable than those visited by the rich. There is strong evidence of inequalities in access, with lower competence among privateand public-sector providers in poor neighborhoods, but no evidence of inequalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 5 publications
0
68
1
1
Order By: Relevance
“…Alternative medicine is often cheaper than modern medicine so poorer populations (such as in Bihar) would be expected to use alternative medicine more often. It has been shown that the quality of health services used by the poor (whether public or private) are of less good quality than those used by the rich in Delhi (Das & Hammer 2007 Returning to our hypotheses, we saw that there was more CHE in Kerala than…”
Section: Impact Of Using Private Healthcare On Che (Stratified By Prementioning
confidence: 66%
“…Alternative medicine is often cheaper than modern medicine so poorer populations (such as in Bihar) would be expected to use alternative medicine more often. It has been shown that the quality of health services used by the poor (whether public or private) are of less good quality than those used by the rich in Delhi (Das & Hammer 2007 Returning to our hypotheses, we saw that there was more CHE in Kerala than…”
Section: Impact Of Using Private Healthcare On Che (Stratified By Prementioning
confidence: 66%
“…22 20 Technically, the exercise is valid as long as the there is payoff-equivalence among the doctors visited and not-visited, the market is competitive, and the observed day was random. 21 Poor and rich patients visit the same private doctors, conditional on living in the same neighborhood (Das and Hammer 2005b). This could indicate that poor patients are, on average, sicker when they visit the doctor and thus their willingness-to-pay is higher than what their income indicates.…”
Section: Across and Within Neighborhood Comparisonsmentioning
confidence: 99%
“…Provider characteristics for different samples are in Table A1. 12 These 35 doctors are no different from the remainder of the sample in observable characteristics, including competence. Details are in Appendix 1.…”
mentioning
confidence: 97%
“…Many authors have addressed the variation in quality-some explicitly looking at the gaps outlined earlier and others addressing the elements within the gaps directly. Das and Hammer (2007) and Leonard, Masatu, and Vialou (2007) examine the variation in the can-do gap across different institutions, showing that the can-do gap is much larger in the public sector than it is in the private or charitable sectors. Whereas Das and Hammer (2007) examine the difference between public and private, Leonard Masatu, and Vialou (2007) show that the gap is related to the degree of decentralization: facilities that are more decentralized in management have smaller can-do gaps than facilities with centralized decision making.…”
Section: Three-gap Model Of Quality Of Carementioning
confidence: 99%
“…Das and Hammer (2007) and Leonard, Masatu, and Vialou (2007) examine the variation in the can-do gap across different institutions, showing that the can-do gap is much larger in the public sector than it is in the private or charitable sectors. Whereas Das and Hammer (2007) examine the difference between public and private, Leonard Masatu, and Vialou (2007) show that the gap is related to the degree of decentralization: facilities that are more decentralized in management have smaller can-do gaps than facilities with centralized decision making. Das and Sohnesen (2007) consider the variation in quality across types of patients, looking for evidence of discrimination (which they do not find).…”
Section: Three-gap Model Of Quality Of Carementioning
confidence: 99%